A method for phase transfer of inorganic nanomaterials by surface modification

Through surface modification and ligand exchange technology, inorganic nanomaterials are uniformly dispersed in organic solvents, solving the problem of difficulty in dispersing inorganic nanoparticles in polymer monomer solutions, and achieving efficient combination of inorganic nanoparticles and polymers. It has wide application prospects.

CN115770883BActive Publication Date: 2025-02-25NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111039342.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-06
Publication Date
2025-02-25
Estimated Expiration
2041-09-06

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly and stably disperse inorganic nanoparticles in polymer monomer solutions, resulting in difficulty in binding to the polymer.

Method used

Inorganic nanomaterials such as gold nanorods, gold particles, gold nanocones, silver nanoparticles or gold-silver dimers in N,N-dimethylformamide (DMF) containing ligands or Phase transfer is performed in dichloromethane (DCM) solution, and ligand exchange is performed using amphiphilic surfactant PVP to impart amphiphilicity to the nanoparticles and thus disperse evenly in the organic solvent.

Benefits of technology

The uniform and stable dispersion of inorganic nanoparticles in organic solvents is achieved, the preparation process is simplified, and the binding efficiency of inorganic nanoparticles and polymers is improved. It is suitable for optical devices, sensors, photocatalysis and biomedicine fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115770883B_ABST
    Figure CN115770883B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for phase transfer of surface-modified inorganic nanomaterials, and belongs to the field of inorganic nanomaterial synthesis. The method uses gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers as research objects, and with the assistance of N,N-dimethylformamide, utilizes the amphiphilic properties (hydrophilicity and hydrophobicity) of polyvinyl pyrrolidone, and can stabilize inorganic metal nanomaterials in non-polar solvent dichloromethane for a long time through rapid transfer. The method does not require long-term ligand exchange and is simple and effective to operate, and further expands other metal nanomaterials, indicating that this phase transfer method has universality in terms of morphology, surface ligands and material components, which provides an important basis for the preparation of various functional materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of inorganic nano material synthesis, in particular to phase transfer of inorganic nano material through surface modification. Background Art

[0002] With the advancement of nanosynthesis technology, nanoparticles of various morphologies can now be synthesized in the laboratory. However, the development of nanotechnology is not only for the purpose of synthesizing nanoparticles of various forms, but also for the hope that nanotechnology can be more widely used in production practice. Polymers have many excellent properties, such as high-strength mechanical properties, excellent optical properties, high ductility, corrosion resistance, etc. Polymers can serve as excellent carriers of inorganic nanomaterials, and loading inorganic nanomaterials into polymers is an important way for them to exert their physical and chemical properties. The doping of inorganic nanomaterials can enhance the strength of polymers or give them electrical conductivity, optics, magnetism or permeability and other functions. This combination of polymer materials and different inorganic nanomaterials is usually called polymer-inorganic nanocomposites.

[0003] There are two methods for preparing inorganic nanocomposite materials. One is that inorganic nanomaterials are synthesized in situ in polymer carriers by themselves, that is, nanomaterial precursors are added to polymer carriers, and polymer inorganic nanomaterials are synthesized under the conditions of light or heating. However, the nanomaterials synthesized by this method cannot control their size, morphology, etc., which cannot give full play to the structural properties of inorganic nanomaterials. Another method is to synthesize uniform nanomaterials first and then disperse them in polymers. However, how to ensure the dispersibility of inorganic nanomaterials in polymers is a key problem that needs to be solved urgently. The reason is that inorganic nanoparticles are usually synthesized in water phase, and polymers or polymer monomer solutions are mostly organic phases, which makes it difficult for inorganic nanoparticles to be uniformly and stably dispersed in polymers or polymer monomer solutions.

[0004] Modifying the surface of inorganic nanomaterials so that they can be uniformly and stably dispersed in the organic phase is an ideal solution to the phase transfer problem. So far, the surface modification methods of metal nanoparticles have included polymer coating, surface grafting polymer brushes, ligand exchange of alkyl alcohols or alkyl amines, and ionic liquid extraction. However, these surface modification methods have various defects, such as long surface modification cycle, complex process, low transfer rate, poor universality, etc.

[0005] Therefore, finding a simple, effective and universal phase transfer method is of great significance for the preparation of inorganic metal nanocomposites. Summary of the invention

[0006] The technical problem solved by the present invention is: to propose a method for making inorganic nanoparticles uniformly and stably dispersed in an organic solvent through surface modification. The method is simple and universal. The phase transfer method solves the problem that inorganic nanoparticles synthesized in the aqueous phase cannot be uniformly and stably dispersed in a polymer monomer solution, making it easier for inorganic nanoparticles to combine with polymers.

[0007] In order to solve the above technical problems, the technical solution proposed by the present invention is: a method for phase transfer of surface modified inorganic nanomaterials, the preparation steps are as follows

[0008] Step (1): synthesizing gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers;

[0009] Step (2): centrifugally purify the gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers and disperse them in a 0.5-1.5 times original volume of a N,N-dimethylformamide (DMF) solution containing a ligand, wherein the ligand is polyvinylpyrrolidone (PVP) and the PVP concentration is 12 mg / ml;

[0010] Step (3): The nanomaterial described in step (2) is centrifuged and purified, and dispersed in a dichloromethane (DCM) solution containing a ligand that does not exceed the initial volume of the nanomaterial, wherein the ligand is PVP and the PVP concentration is 6-12 mg / ml.

[0011] Preferably, the synthesis method of gold nanorods in step (1) is as follows: first, prepare gold nanoparticle seeds in a 20 mL small reaction bottle: add sodium borohydride (NaBH4, 10 mM, 0.3 mL) to a mixture of tetrachloroauric acid (HAuCl4, 0.125 mL, 10 mM) and cetyltrimethylammonium bromide (CTAB, 5 mL, 0.1 M) under stirring conditions, and under vigorous shaking, the color of the solution instantly changes from golden yellow to brown, indicating that gold nanoparticle seeds are formed, and the vortex state is maintained for 10 minutes to allow HAuCl4 to be fully reduced; the prepared seed solution is allowed to stand at room temperature for 2 hours and then used to prepare gold nanorods; 95 mL of CTAB (0.1 M), 1 mL of silver nitrate (AgNO3, 10 mM) and 5 mL of HAuCl4 (10 mM) solution are added to a 250 mL conical flask in sequence. Then, 0.55 mL of L-ascorbic acid (L-AA, 0.1 M) solution was added to the mixture, and the flask was slowly shaken until the solution became colorless; finally, 0.12 mL of seed solution was added to the above mixture under gentle mixing; the resulting mixture was allowed to stand at room temperature overnight to obtain gold nanorods; the gold nanorods were further purified by centrifugation and stabilized in 100 mL of CTAB solution (0.1 M) for further use.

[0012] Preferably, the gold nanoparticle synthesis method in step (1) is as follows: synthesize 15nm gold nanoparticles. First, put 100mL HAuCl4 (0.1mg / mL) aqueous solution into a 250mL two-necked round-bottom flask, then place it in a 130°C oil bath for reflux heating and stirring, and after the HAuCl4 aqueous solution boils, quickly add 3mL sodium citrate (1wt%) aqueous solution thereto. The color of the mixed solution undergoes a transition from colorless, purple, purple-red to finally stabilized in wine red in a short period of time. The appearance of wine red indicates that 15nm gold particles have been formed. Continue heating and boiling for 30 minutes and then cool it to room temperature. Subsequently, 45 mL of deionized water and 10 mL of the above-prepared 15 nm gold nanoparticle solution were mixed in a 250 mL two-necked round-bottom flask, which was placed in an oil bath at 125°C and heated to reflux with stirring. After the solution boiled, 0.25 mL of sodium citrate (1 wt%) aqueous solution and 0.3 mL of HAuCl4 (10 mg / mL) aqueous solution were quickly added thereto in sequence, and the mixture was heated for 30 minutes to completely reduce HAuCl4 to form a gold layer on the seed surface; this step was repeated twice, and finally 1 mL of sodium citrate aqueous solution was added again and refluxed for 10 minutes to stabilize the synthesized gold nanoparticles, and then cooled to room temperature for storage.

[0013] Preferably, the synthesis method of the gold nanocones in step (1) is as follows: first, prepare a gold seed in a 20 mL small sample bottle, and under vigorous stirring at room temperature, rapidly mix a solution of sodium citrate (9.75 mL, 5.128 mM) prepared with fresh ice water, an aqueous solution of hexadecyltrimethylammonium chloride (CTAC, 50 mM, final concentration), and an aqueous solution of HAuCl4 (0.25 mL, 10 mM); the color of the mixed solution changes from light yellow to brown, indicating the formation of the gold seed; after continuous stirring for 2 minutes, transfer the seed solution to Move to an oil bath at 80°C, stir gently and continue heating for 90 minutes, the solution color gradually changes from brown to red; finally, take out the heat-treated seed solution from the oil bath and store at room temperature; add CTAB (50mL, 100mM), HAuCl4 (2.5mL, 10mM), AgNO3 (0.5mL, 10mM) aqueous solution in a 100mL conical flask, then add HCl (1mL, 1M) and L-AA (0.4mL, 100mM), stir for 2 minutes and then add 0.125mL of the above synthesized gold seed solution. Finally, let the growth solution stand at 30°C for 10 hours.

[0014] Preferably, the synthesis method of silver nanoparticles in step (1) is as follows: 10 mL of 15 nm gold nanoparticles and 50 mL of deionized water are added to a round-bottom flask. Heat to reflux in an oil bath at 130° C., and after the solution is heated to boiling, 0.5 mL of sodium citrate (1 wt%) and 0.5 mL of AgNO3 (10 mg / mL) are quickly added under vigorous stirring, and the resulting solution is heated for 30 minutes, and the solution color changes from red to orange. After 30 minutes, the same amount of sodium citrate and AgNO3 are added again and heating is continued for 30 minutes. In the third round, 0.48 mL of sodium citrate and 0.48 mL of AgNO3 are added, and the resulting solution is heated for 1 hour and then cooled to room temperature. Finally, 21.9 mL of water is added to the solution and stored at room temperature away from light.

[0015] Preferably, the synthesis method of the gold-silver dimer in step (1) is as follows: 20 μL of MBIA ligand (1 mM, ethanol configuration) is added to the gold particle solution synthesized in 1 mL of 3, and then the solution is allowed to stand at 60° C. for 2 hours. After cooling to room temperature, 60 μL of hydroquinone (10 mM aqueous solution) and 60 μL of AgNO3 (10 mM aqueous solution) are quickly added to the above solution in sequence, and the mixed solution is allowed to stand at room temperature for not less than 2 hours, so that AgNO3 is fully reduced, and finally nanoparticles with a gold-silver dimer structure are obtained.

[0016] Preferably, the volume of the gold nanorods in step (2) is 40 ml, the centrifugal speed is 5500 rpm, and the centrifugal time is 15 min; after centrifugation to remove the supernatant, 40 ml of PVP-DMF solution is used for dispersion, the concentration of PVP is 12 mg / ml, and the molecular weight of PVP is 40,000.

[0017] Preferably, the centrifugal speed used in step (3) is 4600 rpm and the centrifugal time is 15 min. After removing the supernatant, 300 μl of PVP-DCM solution is used for dispersion, and the concentration of PVP is 6 mg / ml.

[0018] Preferably, one of the gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers is centrifugally purified and then dispersed in an equal volume of N,N-dimethylformamide (DMF) solution containing the ligand.

[0019] The method of phase transfer of inorganic nanomaterials by surface modification comprises the following steps:

[0020] (1) Gold nanorod synthesis method: First, prepare gold nanoparticle seeds in a 20 mL small reaction bottle: add sodium borohydride (NaBH4, 10 mM, 0.3 mL) to a mixture of tetrachloroauric acid (HAuCl4, 0.125 mL, 10 mM) and hexadecyltrimethylammonium bromide (CTAB, 5 mL, 0.1 M) under stirring. Under vigorous shaking, the solution color instantly changes from golden yellow to brown, indicating the formation of gold nanoparticle seeds. Keep the vortex state for 10 minutes to allow HAuCl4 to be fully reduced. The prepared seed solution is left to stand at room temperature for 2 hours and then used to prepare gold nanorods. 95 mL of CTAB (0.1 M), 1 mL of silver nitrate (AgNO3, 10 mM) and 5 mL of HAuCl4 (10 mM) solution are added to a 250 mL conical flask in sequence. Then, 0.55mL L-ascorbic acid (L-AA, 0.1M) solution was added to the mixture, and the flask was slowly shaken until the solution became colorless. Finally, 0.12mL seed solution was added to the above-mentioned mixed solution under gentle mixing. The resulting mixed solution was left to stand overnight at room temperature to obtain gold nanorods. The gold nanorods were further purified by centrifugation and stabilized in 100mL of CTAB solution (0.1M) for further use.

[0021] (2) Transfer the gold nanorods from the aqueous phase to the organic phase. Take 40 ml of gold nanorods, centrifuge at 5500 rpm for 15 min, and remove the supernatant. Re-disperse with 40 ml of 12 mg / ml PVP-DMF solution, centrifuge again at 5500 rpm for 15 min, and remove the supernatant. Re-disperse with 300 μl of 6 mg / ml PVP-DCM solution. At this point, the gold nanorods have been transferred from the aqueous phase to the organic phase.

[0022] Beneficial effects of the present invention:

[0023] (1) This method is simple and universal

[0024] (2) The phase transfer method solves the problem that inorganic nanoparticles synthesized in the aqueous phase cannot be evenly and stably dispersed in the polymer monomer solution, making it easier for inorganic nanoparticles to combine with polymers.

[0025] (3) The selected amphiphilic surfactant PVP can form a coordination effect with the surface of metal nanoparticles through its amino group and quickly exchange ligands in DMF, making the surface of the nanoparticles amphiphilic.

[0026] (4) This ligand exchange method is simple and rapid. Compared with traditional methods, it does not require heating or long-term incubation, and ligand exchange can be performed during the centrifugation process.

[0027] (5) This method uses DMF, an organic solvent miscible with water, as the transition solvent for phase transfer, and utilizes the water absorption of DMF to further remove residual water.

[0028] (6) Polymer-inorganic nanocomposites have great application value in optical devices, sensors, photocatalysis, biomedicine, etc.

[0029] (7) Gold nanorods, gold particles, gold nanocones, silver nanoparticles, and gold-silver dimers can all be transferred from the aqueous phase to the organic phase using this phase transfer method.

[0030] (8) Theoretically, the higher the concentration of PVP, the more stable the nanoparticles after phase transfer. However, excessive residual PVP may interfere with subsequent applications. Based on comprehensive considerations, we selected a PVP concentration of 12 mg / ml in the PVP-DMF solution and a PVP concentration of 6 mg / ml in the PVP-DCM solution.

[0031] (9) In step 2, the PVP concentration is 12 mg / ml. If the concentration is lower than 12 mg / ml, the gold rods tend to aggregate during phase transfer. If the concentration is higher than 12 mg / ml, the concentration is too high and will affect the next step. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings.

[0033] Figure 1 Surface modification of gold nanorods. (a) Optical photo demonstrating the stability of gold nanorods during phase transfer. (b) UV-visible-near infrared absorption spectra of gold nanorods dispersed in different media. Transmission electron microscopy images of gold nanorods stabilized in (c) aqueous solution and (d) dichloromethane.

[0034] Figure 2 Surface modification of gold nanoparticles. (a) Optical photo demonstrating the stability of gold nanoparticles during phase transfer. (b) UV-visible-near infrared absorption spectra of gold nanoparticles dispersed in different media. Transmission electron microscopy images of gold nanoparticles stabilized in (c) aqueous solution and (d) dichloromethane.

[0035] Figure 3 Surface modification of gold nanocones. (a) Optical photo demonstrating the stability of gold nanocones during phase transfer. (b) UV-visible-near infrared absorption spectra of gold nanocones dispersed in different media. Transmission electron microscopy images of gold nanocones stabilized in (c) aqueous solution and (d) dichloromethane.

[0036] Figure 4Surface modification of silver nanoparticles. (a) Optical photo demonstrating the stability of silver nanoparticles during phase transfer. (b) UV-visible-near infrared absorption spectra of silver nanoparticles dispersed in different media. Transmission electron microscopy images of silver nanoparticles stabilized in (c) aqueous solution and (d) dichloromethane.

[0037] Figure 5 Surface modification of gold-silver dimer. (a) Optical photo demonstrating the stability of gold-silver dimer during phase transfer. (b) UV-visible near-infrared absorption spectra of gold-silver dimer dispersed in different media. Transmission electron microscopy images of gold-silver dimer stable in (c) aqueous solution and (d) dichloromethane, respectively.

[0038] Figure 6 This is the CD spectrum of gold nanorod-PUV circularly polarized optical film DETAILED DESCRIPTION

[0039] Example 1

[0040] (1) Gold nanorod synthesis method: First, prepare gold nanoparticle seeds in a 20 mL small reaction bottle: add sodium borohydride (NaBH4, 10 mM, 0.3 mL) to a mixture of tetrachloroauric acid (HAuCl4, 0.125 mL, 10 mM) and hexadecyltrimethylammonium bromide (CTAB, 5 mL, 0.1 M) under stirring. Under vigorous shaking, the solution color instantly changes from golden yellow to brown, indicating the formation of gold nanoparticle seeds. Keep the vortex state for 10 minutes to allow HAuCl4 to be fully reduced. The prepared seed solution is left to stand at room temperature for 2 hours and then used to prepare gold nanorods. 95 mL of CTAB (0.1 M), 1 mL of silver nitrate (AgNO3, 10 mM) and 5 mL of HAuCl4 (10 mM) solution are added to a 250 mL conical flask in sequence. Then, 0.55mL L-ascorbic acid (L-AA, 0.1M) solution was added to the mixture, and the flask was slowly shaken until the solution became colorless. Finally, 0.12mL seed solution was added to the above-mentioned mixed solution under gentle mixing. The resulting mixed solution was left to stand overnight at room temperature to obtain gold nanorods. The gold nanorods were further purified by centrifugation and stabilized in 100mL of CTAB solution (0.1M) for further use.

[0041] (2) Transfer the gold nanorods in the aqueous phase to the organic phase. Take 40 ml of gold nanorods, centrifuge at 5500 rpm for 15 min, and remove the supernatant. Re-disperse with 40 ml of 12 mg / ml PVP-DMF solution, centrifuge at 5500 rpm for 15 min again, and remove the supernatant. Re-disperse with 300 μl of 6 mg / ml PVP-DCM solution. At this point, the gold nanorods have been transferred from the aqueous phase to the organic phase.

[0042] Example 2

[0043] A circularly polarized optical film and a preparation method thereof are prepared by uniformly and stably distributing gold nanorods in a polymer monomer solution through a three-step phase transfer method and combining the gold nanorods with a polyurethane Vitrimer.

[0044] Step 1, gold nanorod synthesis method: First, prepare gold nanoparticle seeds in a small reaction bottle of 20mL: sodium borohydride (NaBH4, 10mM, 0.3mL) is added to a mixture of tetrachloroauric acid (HAuCl4, 0.125mL, 10mM) and hexadecyltrimethylammonium bromide (CTAB, 5mL, 0.1M) under stirring. Under vigorous shaking, the solution color instantly changes from golden yellow to brown, indicating the formation of gold nanoparticle seeds. Keep the vortex state for 10 minutes so that HAuCl4 is fully reduced. The prepared seed solution is left to stand at room temperature for 2 hours and used to prepare gold nanorods. 95mL of CTAB (0.1M), 1mL of silver nitrate (AgNO3, 10mM) and 5mL of HAuCl4 (10mM) solution are added to a 250mL conical flask in sequence. Then, 0.55mL L-ascorbic acid (L-AA, 0.1M) solution was added to the mixture, and the flask was slowly shaken until the solution became colorless. Finally, 0.12mL seed solution was added to the above-mentioned mixed solution under gentle mixing. The resulting mixed solution was left to stand overnight at room temperature to obtain gold nanorods. The gold nanorods were further purified by centrifugation and stabilized in 100mL of CTAB solution (0.1M) for further use.

[0045] Step 2: Transfer the gold nanorods in the aqueous phase to the organic phase. Take 40 ml of gold nanorods, centrifuge at 5500 rpm for 15 min, and remove the supernatant. Re-disperse with 40 ml of 12 mg / ml PVP-DMF solution, centrifuge at 5500 rpm for 15 min again, and remove the supernatant. Re-disperse with 300 μl of 6 mg / ml PVP-DCM solution for further use.

[0046] Step 3: Weigh 750 mg of polyethylene glycol, 25 mg of glycerol, and 3.9 mg of catalyst, heat at 80°C for 30 min, and add 500 μl of tetrahydrofuran to dilute after melting. Then, add 135 μl of hexamethylene diisocyanate and 90 μl of catalyst in sequence under stirring. Finally, add the gold nanorods in (1) under stirring, pour it into the mold, cure at 60°C for 2 hours, and then vacuum dry at 100°C overnight.

[0047] Step 4: Use a hot press to press the gold nanorod-PUV composite material in (3) into a film at a temperature of 145°C and a pressure of 0.15 MPa for 3 minutes. The final film thickness is 0.2-0.4 mm. Figure 1 It can be seen that the UV-visible spectrum of the gold nanorods in the solution after each phase transfer does not have an obvious red shift, and no aggregation is seen in the TEM image, indicating that the phase transfer of the gold nanorods is successful. Figure 6 It can be seen that the gold nanorod-PUV film has a strong circular dichroism.

[0048] Comparative Example 1

[0049] Compared with Example 1, the difference is that the step (2) of Example 1 is gold nanoparticles, and the steps of synthesizing gold nanoparticles are as follows: synthesize 15nm gold nanoparticles. First, put 100mL HAuCl4 (0.1mg / mL) aqueous solution into a 250mL two-necked round-bottom flask, then place it in an oil bath at 130°C and reflux and heat with stirring. After the HAuCl4 aqueous solution boils, quickly add 3mL sodium citrate (1wt%) aqueous solution thereto. The color of the mixed solution undergoes a transition from colorless, purple, purple-red to finally stabilized in wine red in a short period of time. The appearance of wine red indicates that 15nm gold particles have been formed. Continue heating and boiling for 30 minutes and then cool it to room temperature. Subsequently, 45 mL of deionized water and 10 mL of the prepared 15 nm gold nanoparticle solution were mixed in a 250 mL two-necked round-bottom flask, which was placed in an oil bath at 125°C and heated to reflux and stirred. After the solution boiled, 0.25 mL of sodium citrate (1 wt%) aqueous solution and 0.3 mL of HAuCl4 (10 mg / mL) aqueous solution were quickly added thereto in sequence, and the mixture was heated for 30 minutes to completely reduce HAuCl4 to form a gold layer on the seed surface. This step was repeated twice, and finally 1 mL of sodium citrate aqueous solution was added again and refluxed for 10 minutes to stabilize the synthesized gold nanoparticles, and then cooled to room temperature for storage.

[0050] from Figure 3 It can be seen that the color of the solution of gold nanoparticles did not change after each phase transfer, the UV-visible spectrum did not have an obvious red shift, and no aggregation was seen in the TEM image, indicating that the phase transfer of gold nanoparticles was successful.

[0051] Comparative Example 2

[0052] Compared with Example 1, the difference is that the step (2) of Example 1 is gold nanocones, and the synthesis steps of gold nanocones are as follows: first, prepare a gold seed in a 20 mL small sample bottle, and under vigorous stirring at room temperature, quickly mix NaBH4 (0.25 mL, 25 mM) prepared with fresh ice water, sodium citrate solution (9.75 mL, 5.128 mM) prepared with hexadecyltrimethylammonium chloride aqueous solution (CTAC, 50 mM, final concentration) and HAuCl4 aqueous solution (0.25 mL, 10 mM). The color of the mixed solution changes from light yellow to brown, indicating the formation of gold seeds. After continuous stirring for 2 minutes, the seed solution is transferred to an oil bath at 80°C, and heated for 90 minutes with gentle stirring. The color of the solution shows a gradual change from brown to red. Finally, the heat-treated seed solution is taken out of the oil bath and stored at room temperature. In a 100 mL conical flask, CTAB (50 mL, 100 mM), HAuCl4 (2.5 mL, 10 mM), and AgNO3 (0.5 mL, 10 mM) aqueous solutions were added in sequence, followed by HCl (1 mL, 1 M) and L-AA (0.4 mL, 100 mM), and after stirring for 2 minutes, 0.125 mL of the synthesized gold seed solution was added. Finally, the growth solution was allowed to stand at 30 ° C for 10 hours.

[0053] from Figure 4 It can be seen that the color of the solution of the gold nanocones did not change after each phase transfer, the UV-visible spectrum did not have an obvious red shift, and no aggregation was seen in the TEM image, indicating that the phase transfer of the gold nanocones was successful.

[0054] Comparative Example 3

[0055] Compared with Example 1, the difference is that the silver nanoparticles in step (2) of Example 1 are silver nanoparticles. The synthesis steps of silver nanoparticles are as follows: 10mL 15nm gold nanoparticles and 50mL deionized water are added to a round-bottom flask. Heat to reflux in an oil bath at 130°C. After the solution is heated to boiling, 0.5mL sodium citrate (1wt%) and 0.5mL AgNO3 (10mg / mL) are quickly added under vigorous stirring. The resulting solution is heated for 30 minutes, and the solution color changes from red to orange. After 30 minutes, the same amount of sodium citrate and AgNO3 are added again and continued to heat for 30 minutes. In the third round, 0.48mL sodium citrate and 0.48mL AgNO3 are added, and the resulting solution is heated for 1 hour and then cooled to room temperature. Finally, 21.9mL water is added to the solution and stored at room temperature away from light.

[0056] from Figure 5It can be seen that the solution color of the silver nanoparticles did not change after each phase transfer, the UV-visible spectrum did not have an obvious red shift, and no aggregation was seen in the TEM image, indicating that the phase transfer of the silver nanoparticles was successful.

[0057] Comparative Example 4

[0058] Compared with Example 1, the difference is that the step (2) of Example 1 is a gold-silver dimer, and the steps of synthesizing the gold-silver dimer are as follows: 20 μL of MBIA ligand (1 mM, ethanol configuration) is added to 1 mL of the gold particle solution synthesized in Example 2, and then the solution is placed at 60° C. for 2 hours. After cooling to room temperature, 60 μL of hydroquinone (10 mM aqueous solution) and 60 μL of AgNO3 (10 mM aqueous solution) are quickly added to the above solution in sequence, and the mixed solution is placed at room temperature for not less than 2 hours to allow AgNO3 to be fully reduced, and finally nanoparticles with a gold-silver dimer structure are obtained.

[0059] from Figure 5 It can be seen that the solution color of silver nanoparticles did not change after each phase transfer, the UV-visible spectrum did not have an obvious red shift, and no aggregation was seen in the TEM image, indicating that the phase transfer of gold-silver dimers was successful.

[0060] The present invention is not limited to the specific technical solutions described in the above embodiments, and all technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A method for phase transfer of inorganic nanomaterials by surface modification, characterized in that: The preparation steps are as follows Step (1): synthesizing gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers; Step (2): centrifugally purify the gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers, and disperse them in a 0.5-1.5 times original volume of a N,N-dimethylformamide DMF solution containing a ligand, wherein the ligand is polyvinylpyrrolidone (PVP) at a concentration of 12 mg / ml; Step (3): the nanomaterials described in step (2) are centrifuged and purified, and dispersed in a dichloromethane (DCM) solution containing a ligand not exceeding the initial volume of the nanomaterials, wherein the ligand is PVP, and the PVP concentration is 6-12 mg / ml; The synthesis method of gold nanorods in step (1) is as follows: first, prepare gold nanoparticle seeds in a 20 mL small reaction bottle: add 10 mM sodium borohydride NaBH4 in a volume of 0.3 mL to a mixture of 10 mM HAuCl4 in a volume of 0.125 mL and 0.1 M cetyltrimethylammonium bromide in a volume of 5 mL under stirring. Under vigorous shaking, the color of the solution instantly changes from golden yellow to brown, indicating the formation of gold nanoparticle seeds. Keep the vortex state for 10 minutes to allow HAuCl4 to be fully reduced. After the prepared seed solution is allowed to stand at room temperature for 2 hours, it is used to prepare gold nanorods. 95 mL of 0.1 M CTAB, 1 mL of 10 mM silver nitrate AgNO3 and 5 mL of 10 mM HAuCl4 solution are added to a 250 mL conical flask in sequence. Then, 0.55 mL of 0.1 M CTAB is added to the mixture. M L-ascorbic acid L-AA solution, slowly shake the flask until the solution becomes colorless; finally, add 0.12 mL of seed solution to the above mixture under gentle mixing; the resulting mixture is left to stand at room temperature overnight to obtain gold nanorods; the gold nanorods are further purified by centrifugation and stabilized in 100 mL of 0.1 M CTAB solution for further use; The synthesis method of gold nanoparticles in step (1) is as follows: synthesize 15 nm gold nanoparticles; first, put 100 mL of 0.1 mg / mL HAuCl4 aqueous solution into a 250 mL two-necked round-bottom flask, then place it in an oil bath at 130 °C for reflux heating and stirring, and after the HAuCl4 aqueous solution boils, quickly add 3 mL of 1 wt% sodium citrate aqueous solution thereto, and the color of the mixed solution undergoes a transition from colorless, purple, purple-red to finally stabilized at wine red in a short period of time. The appearance of wine red indicates that 15 nm gold particles have been formed, and continue to heat and boil for 30 minutes before cooling it to room temperature; then, take 45 mL of deionized water and 10 mL of the above-prepared 15 nm gold nanoparticle solution and mix them in a 250 mL two-necked round-bottom flask, place it in an oil bath at 125 °C for reflux heating and stirring, and after the solution boils, quickly add 0.25 mL of 1 wt% sodium citrate aqueous solution and 0.3 mL of HAuCl4 aqueous solution with a concentration of 10 mg / mL, and the mixture was heated for 30 min to completely reduce HAuCl4 to form a gold layer on the seed surface; this step was repeated twice, and finally 1 mL of sodium citrate aqueous solution was added again and refluxed for 10 min to stabilize the synthesized gold nanoparticles, and then cooled to room temperature for storage.

2. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: The synthesis method of gold nanocones in step (1) is as follows: first, prepare a gold seed in a 20 mL small sample bottle, and under vigorous stirring at room temperature, quickly mix a 0.25 mL volume of fresh ice water with a concentration of 25 mM NaBH4, a 50 mM hexadecyltrimethylammonium chloride aqueous solution (CTAC) with a volume of 9.75 mL and a concentration of 5.128 mM sodium citrate solution, and a 0.25 mL volume and a concentration of 10 mM HAuCl4 aqueous solution; the color of the mixed solution changes from light yellow to brown, indicating the formation of gold seeds; after continuous stirring for 2 minutes, transfer the seed solution to an oil bath at 80 ° C, and continue heating for 90 minutes with gentle stirring, and the color of the solution gradually changes from brown to red; finally, remove the heat-treated seed solution from the oil bath and store it at room temperature; add 50 mL of 100 mM CTAB, 2.5 mL of 10 mM HAuCl4, a 0.5 mL aqueous solution with a concentration of 10 mM AgNO3, followed by 1 mL of 1 M HCl and 0.4 mL of 100 mM L-AA. After stirring for 2 minutes, 0.125 mL of the above-synthesized gold seed solution was added; finally, the growth solution was allowed to stand at 30 °C for 10 hours.

3. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: The synthesis method of silver nanoparticles in step (1) is as follows: add 10 mL of 15 nm gold nanoparticles and 50 mL of deionized water to a round-bottom flask; heat to reflux in an oil bath at 130°C, and after the solution is heated to boiling, quickly add 0.5 mL of 1 wt% sodium citrate and 0.5 mL of 10 mg / mL AgNO3 under vigorous stirring, and heat the resulting solution for 30 minutes, and the color of the solution changes from red to orange; after 30 minutes, add the same amount of sodium citrate and AgNO3 again and continue heating for 30 minutes; in the third round, add 0.48 mL of sodium citrate and 0.48 mLAgNO3, heat the resulting solution for 1 hour and then cool it to room temperature; finally, add 21.9 mL of water to the solution and store it at room temperature away from light.

4. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: The synthesis method of the gold-silver dimer in step (1) is as follows: add 20 µL of 1 mM MBIA ligand to 1 mL of the gold particle solution synthesized in 3, and then place the solution at 60 ° C for 2 hours; after cooling to room temperature, 60 µL of 10 mM hydroquinone and 60 µL of 10 mM AgNO3 aqueous solution are quickly added to the above solution in sequence, and the mixed solution is placed at room temperature for not less than 2 hours to allow AgNO3 to be fully reduced, thereby finally obtaining gold-silver dimer structure nanoparticles.

5. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: The volume of the gold nanorods in step (2) is 40 ml, the centrifugal speed is 5500 rpm, and the centrifugal time is 15 min. After the supernatant is removed by centrifugation, 40 ml of PVP-DMF solution is used for dispersion, the concentration of PVP is 12 mg / ml, and the molecular weight of PVP is 40,000.

6. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: The centrifugal speed used in step (3) is 4600 rpm and the centrifugal time is 15 min. After removing the supernatant, 300 μl of PVP-DCM solution is used for dispersion, and the concentration of PVP is 6 mg / ml.

7. The method for phase transfer of inorganic nanomaterials by surface modification according to claim 1, characterized in that: Gold nanorods, gold particles, gold nanocones, silver nanoparticles, or gold-silver dimers are centrifugally purified and then dispersed in an equal volume of a ligand-containing N,N-dimethylformamide DMF solution.

Citation Information

Patent Citations

  • Synthesis method of Au nano material base on phase transfer method

    CN109434133A

  • Sea-urchin-shaped gold nano particles and synthesis method thereof

    CN110039068A